Electricity generation comparison of food waste-based bioenergy with wind and solar powers: A mini review - Ngoc Bao Dung Thi; Chiu-Yue Lin; Gopalakrishnan Kumar (Sustainable Environment Research, 2016)
The food waste treatment-based anaerobic digestion has been proven to play a primary role in electricity industry with high potentially economic benefits, which could reduce electricity prices in comparison with other renewable energy resources such as wind and solar power. The levelized costs of electricity were reported to be 65, 190, 130 and 204 US$ MWh−1 for food waste treatment in anaerobic landfill, anaerobic digestion biogas, solar power, and wind power, respectively. As examples, the approaches of food waste treatment via anaerobic digestion to provide a partial energy supply for many countries in future were estimated as 42.9 TWh yr−1 in China (sharing 0.87% of total electricity generation), 7.04 TWh yr−1 in Japan (0.64% of total electricity generation) and 13.3 TWh yr−1 in the US (0.31% of total electricity generation). Electricity generation by treating food waste is promised to play an important role in renewable energy management. Comparing with wind and solar powers, converting food waste to bioenergy provides the lowest investment costs (500 US$ kW−1) and low operation cost (0.1 US$ kWh−1). With some limits in geography and season of other renewable powers, using food waste for electricity generation is supposedly to be a suitable solution for balancing energy demand in many countries.